Congenital Anomalies in Newborn Infants Clinical and Etiopathological Perspectives - Verma, Rita P. (IntechOpen, 2021)
Congenital anomalies constitute a large group of diverse biochemical, histological, and anatomical defects presenting at birth and caused by a myriad of inherently unrelated etiopathogenic factors. A significant number of cases are idiopathic. With striking variability in clinical manifestation, the outcomes range from inconsequential to lethal, with immense medical, social, emotional, and financial implications. The principles of management vary from medical, surgical, none, or both, and the surgical procedures can be lifesaving or merely cosmetic. This book discusses the epidemiology, etiopathogenesis, recurrence risk, and specific clinical and investigational evaluation of congenital malformations. In addition, the book reviews the embryology, anatomy, pathophysiology, and updated management concepts of some of the most complex and intriguing anomalies of the major organ systems.